Perencanaan Desain Tugu Batas Desa Ujan Mas Kota Pagar Alam - Rosyani Dwi Sastika Putri; Debby Sinta Devi; Mukhlis Nahriri Bastam; Ahmad Khoirul (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2025)
The construction of the village boundary monument is a form of community service that aims to provide clarity on the administrative boundaries of an area and strengthen village identity. This activity was carried out by lecturers and students of Indo Global Mandiri University in Ujan Mas Village, Jangkar Mas Village, Pagar Alam City, South Sumatra Province, considering that this village does not have a clear boundary marker. The method of implementing this activity consists of several stages, namely location surveys, designing designs using AutoCAD, preparing a Budget Plan (RAB) with Microsoft Excel, making 3D designs using SketchUp and building monuments according to agreed designs. The survey was conducted to determine the strategic location in accordance with the administrative boundaries of the village, while the design was made by considering the aesthetic aspects and character of the village. The preparation of the RAB aims to manage cost needs effectively, so that development can run according to the available budget, the Budget Plan needed for the construction of the village boundary monument is IDR 9,526,500. The result of this activity is a village boundary monument that not only functions as an area marker, but also as a symbol of village identity that strengthens cultural values and clarifies administrative boundaries. The existence of this monument is expected to support more organized regional management and provide long-term benefits for the Ujan Mas Village community.